Turaṡ, Geografi, dan Aransemen Kronologis: Studi Tafsir Nuzūlī dan Kesadaran Historis Mufasir - Pratama, Aziz Bashor (Contemporary Quran, 2024)
This study is driven by the variations in the chronological arrangement of the Qur'an among different nuzūlī tafsirs, reflecting the reasoning systems of interpreters in engaging with the turaṡ tradition. The aim of this research is to explore how geographical contexts shape the reasoning and awareness of mufasirs regarding the discourse on Qur'anic historicity. Utilizing a literature review method, the study examines five nuzūlī tafsirs as primary sources, complemented by relevant secondary research. Foucault's theoretical framework and comparative media analysis are employed to investigate the interactions among nuzūlī tafsirs concerning the Qur'an's chronological arrangement, aiming to uncover the underlying factors behind these differences. The findings reveal that historical awareness and the concept of tartīb al-nuzūl in the modern era have led interpreters to reexamine the chronological debates of the Qur'an. Interpreters from the Arab-Syrian context tend to adopt the turaṡ reasoning system to uphold Islamic identity within the global intellectual landscape, while Al-Jābirī, drawing from the French philosophical tradition, critiques this historical reliance through a deconstructive lens. This epistemic confrontation indicates that discussions on the Qur'an's chronological arrangement remain pertinent for reconstruction, with geographical knowledge significantly influencing the diverse reasoning of interpreters.